2014
DOI: 10.1111/nicc.12106
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Empowerment Scale for ICU patients' families: an instrument development study

Abstract: Knowledge of families' empowerment status may help to address their psychological needs and their ability to provide family support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A particularly important finding supporting our conclusion of the acceptability validity and trustworthiness of our methods is the increase in consensus from the first to second Delphi round for the expert panel (Zeng & Li, ). Further evidence is found in our high coordination coefficient showing strong agreement on symptom‐items among experts (Li et al., ). High levels of expert consensus allowed us to delete, revise or add symptoms without decreasing the consistency of the measure (Liu, ; Roberts‐Davis & Read, ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A particularly important finding supporting our conclusion of the acceptability validity and trustworthiness of our methods is the increase in consensus from the first to second Delphi round for the expert panel (Zeng & Li, ). Further evidence is found in our high coordination coefficient showing strong agreement on symptom‐items among experts (Li et al., ). High levels of expert consensus allowed us to delete, revise or add symptoms without decreasing the consistency of the measure (Liu, ; Roberts‐Davis & Read, ).…”
Section: Discussionsupporting
confidence: 70%
“…Senior health professionals, working independently, reached acceptable levels of consensus on early symptoms of PSD that are both clinically important and clinically specific in the acute stroke patients. The statistical consensus parameters used to determine the overall expert agreements met or exceeded acceptable levels reported in similar research protocol (Li et al., ).…”
Section: Discussionmentioning
confidence: 78%
“…Skills are developed through training and reflection, and contribute to a belief in one's own ability to sufficiently handle a situation or influence events . In an empowering critical care environment, individuals can mediate assistance or guidance that supports skill development .…”
Section: Resultsmentioning
confidence: 99%
“…Available critical care instrument validation studies using CVI quantification have reported a range of critical care working experience from five 33 to 10 years. 34 Although the criterion for inclusion in our study as a nurse expert was a minimum of 2 years of critical care experience, our panel of expert judges averaged more than a decade of experience working in the ICU (Table 2), during which time they accumulated the knowledge and expertise to contribute effectively to this content validation study.…”
Section: Discussionmentioning
confidence: 99%